The cost of mental health: A socio-psycho analysis - Goswami, Sribas (IASSI Quarterly: Contributions To Indian Social Science)
A human being is endowed with numerous abilities, mental, intellectual, social temperamental, motivational, and attitudinal. But still, some person is found deficient in some of the abilities. They suffer even from the prenatal stage as a result of which they are born with several disabilities in mental and even in physical aspects. The society has the responsibility to take care of the specific deficiencies so that they can utilize their capacity to the maximum and be a part of mainstream society. The study assesses and compares the family burden, social support, marital quality of life, Social Stigma and self-esteem of parents of children with intellectual disability and children with blindness, and to correlate socio-demographic and clinical variables with family burden, social support, marital quality of life, social stigma and self-esteem parents of children with intellectual disability and children with blindness. The results show that there was a significant difference between the two groups with regard to class and type of school and shows that age at first recognized, among the psycho social variables there is a statistically significant difference between the two groups in the domains of family burden. There is a difference between the two groups in other psycho social variables like self-esteem, marital life, social support and social stigma but they are not statistically significant. It can be concluded from the study that the parental psycho social problems are found to be not much severe in this study.- Reproduced
Keywords: Family burden, Social support, Quality of life, Social stigma, Self-esteem, Intellectual disability